Comparison between simplex roller gauge of 40.5×50×52 mm and 39.5×49.5×50.5 mm - E Karim, Fahmida; Redwanul Islam, Md. (International Journal of Engineering and Technology, 2022)
Simplex machine plays a vital role in spinning process. By using simplex machine the roving has been found, which reduced maximum draft in the ring frame. So it is necessary to produce good qualities roving from simplex machine. For this reason the draft and amount of false twist has been kept at a particular ration. For controlling draft, the drafting arrangement needed to arrange in a proper order. The gauge distance between the drafting zones are needed to maintain at a particular distance, through which the production and the quality of the product will be optimum level. Here for the research work the simplex machine drafting arrangement is 4 over 4 and diameter of the rollers are 28.5 mm. For this reason three drafting zones have been formed, they are front, middle and back zone. Here the roving hank has been used is 0.80 and this roving is used for producing 26 Ne and 32 Ne cotton carded yarn. By using the same roving hand and changing the gauge distances, itâ€™s easily identified which gauge distance is suitable for producing roving as well as the quality of ring yarn.Â Â